2008
DOI: 10.1159/000127361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sevelamer on the Progression of Vascular Calcification in Patients on Chronic Haemodialysis

Abstract: Background/Aim: Vascular calcification is thought to be associated with a high cardiovascular mortality rate in patients with end-stage renal disease. Control of hyperphosphataemia is important for the treatment of the vascular calcification. The aim of the present study was to evaluate the effects of sevelamer hydrochloride on the progression of aortic calcification in haemodialysis (HD) patients. Methods: 42 HD patients were studied in this study and divided into two groups (sevelamer vs. calcium). Sevelamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 28 publications
0
45
0
1
Order By: Relevance
“…Eighteen trials 4,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] met the predefined inclusion criteria and were included in our meta-analysis ( Figure 1). The 18 trails included 3676 patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen trials 4,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] met the predefined inclusion criteria and were included in our meta-analysis ( Figure 1). The 18 trails included 3676 patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 18 trails included 3676 patients (Table 1). CAC score was reported 4,9,10,[15][16][17][18][19][20][21]23,24,[27][28][29] After adjustment for the agreement between reviewers, the j coefficient on the agreement of the included studies was 0.92 (95% confidence interval 0.83 to 0.95), suggesting good agreement between reviewers in data extraction. All studies were randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the reasons for exclusion of 20 of these reports. Ultimately, we included 14 trials, all performed between 1999 and 2008, that enrolled a total of 3,271 HD patients [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. None of the conference abstracts met the inclusion criteria and therefore were not included for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple publications were excluded from the count of included studies because they were secondary publications of previous reports; however, any relevant and unique results were extracted and included. They compared sevelamer with either calcium acetate [18,20,21,24,25,26] or calcium carbonate [19,22,23,27,28] or both (based on physician preference) [15,16,17]. The treatment durations ranged from 8 weeks to 45 months.…”
Section: Resultsmentioning
confidence: 99%
“…Slowing the progression of VC would be a desirable goal, since clinical reversibility has not been proven yet [143,159] . Several careful prospective randomized studies performed in both prevalent and incident hemodialysis patients [19,20,160] , although not all studies [57] , have demonstrated that sevelamer attenuates the progression of coronary and aortic artery calcifications as compared with calcium-based phosphorus binders. The TTG (Treat to Goal) and RIND studies showed also that the baseline calcification burden is one of the most important predictors of the rate of progression.…”
Section: The Role Of Vcs In Treatment Decisionsmentioning
confidence: 99%